Analisis Manajemen Risiko Dengan Menggunakan Framework ISO 31000:2018 Pada Sistem Informasi Gudang - Wirawan Harefa; Kristoko Dwi Hartomo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
CV Ribka Furniture is a company that is involved in the production and sales of shelves, cabinets, chairs, sofas, tables and so on, the company has implemented IS/IT in optimizing business activities to be more effective and efficient. The company uses an ERP application that aims to control all production processes such as recording incoming goods, outgoing goods, total stock of goods, as well as being integrated with other divisions such as payroll, attendance, and so on. However, it is undeniable that there are always possible risks that may occur and may interfere with business activities in the use of related systems. In this case, risk analysis is needed for IS/IT resources contained within the company. Applying ISO 31000 analysis is expected to minimize the risks that may exist in ERP applications. The results of this risk analysis are in the form of an analysis of the possibility of existing risks, evaluations, to risk mitigation plans so that they can produce improvements to existing risks, so the company can adjust to the priorities of the existing risk levels, so as not to interfere with business activities at CV Ribka Furniture